Práticas de leitura em uma sala de aula da Escola do Assentamento: educação do Campo em construção - Vania Aparecida Costa (2010)
This research aims to comprehend classroom reading practices in an agrarian reform settlement organized by Movimento dos Trabalhadores Rurais Sem Terra (MST) in the region of Rio Doce Valley, Minas Gerais, Brazil. The study was prompted by the ever-increasing importance of studies on literacy practices (Street, 1984; Brandt, 2002; Kleiman, 1995; Goulart, 2006) as a part of a process of comprehending the relation between education, language and writing (Soares, 1996, 1998; Gnerre, 1987) and articulating the relation between literacy, low-income families and writing. The MST has played a vital role since its inception, 25 years ago, in raising awareness for rural education and have represented themselves as a collective that sees the rural setting as a historic space of land dispute and education (Caldart, 2004; Arroyo, 2004; Fernandes & Molina, 2004; Ribeiro, 2007). In this context, there are grounds for researches focusing on formal educational practices and an inquiry on classroom literacy practices. To do so, a field research was carried out, with ethnographic methodology (Heath, 1982 and 1983; Rockwell, 1987 and 2009) in one group of Grammar school students in a settlement school. Analysis of reading events were directed by notions of appropriation (Chartier, 1990) and enunciation (Bakhtin, 1995 and 2006), defined from Heath's literacy events (1982 and 1983) adapted in Brazil by Kleiman (1995) and Marinho (1995). Literary texts were differentiated from non-literary texts in this set of events, expressing the value of literary literacy (Paulino, 2001) for this group. Elements of the reading events such as the materiality of the text, reading methods and teacher-student interaction mediated by texts, as well as reading beliefs (Rockwell, 2001) showed, in the developing literacy practices, the dialectic between local and global contexts, between oral and written communication, between the State and the social movement. They also indicate the need to assume, in the comprehension of developing literacy practices in classrooms of settlement schools, the expressible dialectic between, from one side, the state/education/schooling culture/writing, a relation specific to a social project constructed and championed for the past hundred years in Brazil, that is, a universal model of literacy; and from the other, the appropriation writing/speaking/education/social movement, a relation identified in the classroom that needs to be strengthened, reflected upon and expanded in an educational project tackling knowledge and social values such as rural education and its negotiation with MST pedagogy and low-income education.